Oral respiration modulates sensory and cognitive brain potentials differently than nasal respiration - Viviana Leupin; Juliane Britz (Scientific Reports)
Abstract Respiration influences brain activity and awareness through two mechanisms: direct rhythmic entrainment via olfactory bulb (OB) stimulation and indirect modulation through baroreceptor (BR) activity fluctuations that affect cortical excitability. During nasal breathing, both mechanisms are active and can influence sensory event-related potentials (ERPs). To isolate the contribution of BR activity, we tested the same paradigm during oral breathing, which eliminates OB stimulation. Results showed that sensory ERPs varied with the cardiac (with delayed timing) but not with the respiratory phase. The P3a component was modulated by awareness only when BR activity was low (during inhalation and diastole), while the visual awareness negativity (VAN) and P3b were modulated by awareness across all conditions. These findings indicate that BR fluctuations alone cannot fully account for the respiratory modulation of awareness-related ERPs, but they require entrainment of brain activity modulated by mechanical OB stimulation.